Factors Influencing Self-Efficacy and Adoption of ICT Dissemination Tools by New Extension Officers - Wayne G. Ganpat; Jeet Ramjattan; Robert Strong (Journal of International Agricultural and Extension Education, 2016)
Information Communication Technologies (ICTs) offer Extension systems opportunities to expand participation and provide information faster to stakeholders. The study included fifty-seven new extension officers drawn from the public, private and state assisted extension organizations in Trinidad. Participants were surveyed to assess their level of confidence in the use of ICTs and the factors that impacted their use of these dissemination tools. The survey, which was conducted during March to May 2015 on themandatory office days of the agents, consisted of five sections which captured socio demographic variables, performance expectancy, effort expectancy, social influence and self-efficacy in the use of ICTs. Percentages and means were used to describe the data set and multiple regression analysis was used to explore relationships with ICT use. Results showed that: use of ICTs was moderate; the professional level of officers, their education level, perceptions of ICTs as useful and easy to use and social influence significantly impacted their use of ICTs in their job functions. There are implications for the provision of quality and timely delivery of information to clients. It is recommended that the entry level requirements for new officers should be raised by employers, in-service training in ICTs and other modern communication methods and tools be provided to those already in the system, and the curricula at the main tertiary training institution be reviewed to include ICTs for extension work
Keywords: Extension officers; Information and Communication Technologies; Trinidad; adoption